Volcanic Moon theory Is TES and TEV applicable to other celestial bodies? - Valverde Ramírez, Claudio (2022)
When assessing what is stated in the Seismic Energy Theory (TES) and the Volcanic Energy Theory (TEV) (among other details, they specify the importance of analyzing the Earth as a whole, that is, as a body) we reflect that for them to be universal theories they must be applicable to other celestial bodies or at least provide us with some answers by analogy. For this reason, we will mainly focus on studying our natural satellite, the Moon, because due to its proximity to Earth it is the celestial body about which we have the most information, not being able to avoid making a referential analysis with other celestial bodies. The investigation reveals that the Moon has had the conditions for a very intense volcanic activity, as a result of which the consummation of the reactive components has been in less time (compared to the terrestrial volcanic activity), therefore, unlike On the Earth, on the Moon the volcanic activity soon ceased, leaving traces that reflect that violent past with abundant active volcanic cones, enough to form seas of lava that are preserved to this day, those of us who observe them in a gray environment of apparent eternity.